Epidemiology and evolution of the genetic variability of Anaplasma marginale in South Africa. - (:unkn) unknown (My University, 2014)
Contribution: Study design, supervision, molecular and phylogenetic analysis A. marginale; MSP1a; Prevalence; Selective pressures; MSP1a vaccines
Keywords: African Research